Implementation of UPFC, UPFC Along with PI and Fuzzy Based Controllers in Three Area Interconnected Power Systems for Load Frequency Control (International Journal of Innovative Research in Computer Science & Technology, 2022)
In this paper, the author intends to present  the application of Unified Power Factor Controllers (UPFC)  to control the frequency of three area interdependent and  interconnected reheat and hydro systems by controlling the  frequency of the system under disturbance due to load  variations. Efficacy of the PID controllers to regulate the  system dynamics has already been analyzed. By the use of  fuzzy logic controllers, the system dynamics is further  enhanced and the furtherance in the results is ascertained.  This paper also demonstrates the superiority of Fuzzy Logic  Controller (FLC) in connection with PID controllers and the  UPFC. This paper also discusses the mathematical model of  the system.
Keywords: Static Synchronous Series Compensator (SSSC); Static Synchronous Compensator (STATCOM; Load Frequency Control (LFC); PID Controller; Fuzzy Logic Controller